2009
DOI: 10.1093/sleep/32.12.1629
|View full text |Cite
|
Sign up to set email alerts
|

Dream-Enacting Behaviors in a Normal Population

Abstract: Dream-enacting behaviors are prevalent in healthy subjects and sensitive to question wording but not social desirability. Subtypes are related, differ with gender and occur independently of other parasomnias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 14 publications
4
41
0
2
Order By: Relevance
“…Surveys have revealed that some DEB by clinical history alone is nearly universal. In a study of 1140 college-aged students, 98% acknowledged a history of at least 1 DEB symptom [106]. DEB is particularly common in recently postpartum women [107].…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Surveys have revealed that some DEB by clinical history alone is nearly universal. In a study of 1140 college-aged students, 98% acknowledged a history of at least 1 DEB symptom [106]. DEB is particularly common in recently postpartum women [107].…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Details about the battery and results from some of the questionnaires are published elsewhere (Nielsen & Kuiken, 2013;Nielsen et al, 2009), and only some of the findings are described here. Subjects responded to questionnaires on optically scored answer sheets; these were subsequently scanned and verified by an assistant to remove cases with incorrectly coded or out of range responses.…”
Section: Methodsmentioning
confidence: 99%
“…Dream-enacting behaviors are frequently the culmination of highly disturbing dreams, including the typical nightmares of college students (Nielsen, Svob, & Kuiken, 2009), the unpleasant 'baby-in-peril' dreams of postpartum mothers (Nielsen & Paquette, 2007), and the violence-filled nightmares of patients with REM sleep behavior disorder (RBD) (Schenck, Bundlie, Ettinger, & Mahowald, 1986;Schenck, Lee, Bornemann, & Mahowald, 2009). However, it is unknown whether a propensity for mirroring others' emotions and behaviors while awake is associated specifically with self-reported nightmare frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Nielsen found that the prevalence of various behaviours particularly sexual behaviours apparently increased if respondents were asked specific questions about the behaviour; subjects did not readily reveal their sexual behaviour without being asked. Overall Nielsen noted that "females reported more speaking, crying, fear and smiling/laughing than did males; males reported more sexual arousal" [58].…”
Section: Sleep-related Sexual Behaviourmentioning
confidence: 99%